2013
DOI: 10.3352/jeehp.2013.10.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment methods in surgical training in the United Kingdom

Abstract: A career in surgery in the United Kingdom demands a commitment to a long journey of assessment. The assessment methods used must ensure that the appropriate candidates are selected into a programme of study or a job and must guarantee public safety by regulating the progression of surgical trainees and the certification of trained surgeons. This review attempts to analyse the psychometric properties of various assessment methods used in the selection of candidates to medical school, job selection, progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
32

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 37 publications
0
8
0
32
Order By: Relevance
“…2 Summative assessments are used for selection and certification. Figure 4 highlights various points of assessment during surgical training in the UK, the most important of which are the Member of the Royal College of Surgeons (MRCS) and Fellow of the Royal College of Surgeons (FRCS) examinations.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Summative assessments are used for selection and certification. Figure 4 highlights various points of assessment during surgical training in the UK, the most important of which are the Member of the Royal College of Surgeons (MRCS) and Fellow of the Royal College of Surgeons (FRCS) examinations.…”
Section: Assessmentmentioning
confidence: 99%
“…2 Research has shown that the mini-clinical evaluation exercise (mini-CEX), case-based discussion (CbD), direct observation of procedural skills (DOPS) and the mini-peer assessment tool (mini-PAT) are feasible, reliable and valid assessment methods 50–52. Observational tools such as the use of procedure-based assessments (PBA) during real procedures and objective structured assessment of technical skills (OSATS) during simulated procedures have also shown good validity and reliability 53…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The manner in which both undergraduate and postgraduate medical graduates are assessed has been subject to extensive scrutiny and review in recent years. [1][2][3][4][5] The traditional format of examination with written essay-type papers, clinical cases and oral viva voce examinations have been criticised by educationalists and found to be significantly flawed. 6,7 These formats of examination are unfortunately extremely subjective and lack the psychometric properties of a good examination such as reliability, validity, applicability and acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical performance, competence, and skill acquisition can be measured through various assessment methods, broadly categorised into formative and summative, where former is aimed at providing feedback on the performance and latter is used to formally assess the acquisition of the skills required for completion of the training (Evgeniou 2013). The majority of assessment tools in surgical training are subjective and most of these tools are checklists (Alkhayal et al 2012), for example the Structured Technical Skills Assessment Form (STSAF) (Winckel et al 1994).…”
Section: Introductionmentioning
confidence: 99%